Actualization of Leaders Interpersonal Intelligence in Quality Development of The Ahlul Qur - Putra, Fadli Padila; Prastowo, Andi (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2024)
To help leaders develop the quality of Ahlul Qur'an Tahfizh House, this study tries to ascertain how the dimensions of social sensitivity, social insight, and social communication have been implemented. This study uses a descriptive qualitative research design and uses observation, interviews, and documentation as data collection methods. Data reduction, data presentation, and data verification are the stages of analysis used. The results are: first, there is an actualization or real manifestation of the social sensitivity dimension in the form of empathy, social sensitivity, showing respect, and giving appreciation to ustadz/ustadzah and students of Ahlul Qur'an Tahfizh House. Second, the actualization of the social insight dimension in the form of the ability to handle the problems faced. Third, the actualization of the social communication dimension in the form of the ability to establish communication with the residents of the Ahlul Qur'an Tahfizh House to achieve institutional goals. These forms of actualization